Ten years after: capital flows and the global monetary order*. Issue 2 (September 2019) - Reininger, Thomas; Schuberth, Helene; Wögerer, Michael
Abstract : Cross-border bank flows, which had surged in the run-up to the global financial crisis (GFC), shrank significantly after the GFC. According to our findings, this development did not point to financial deglobalization, as was widely expected. Instead, it reflected a cross-border deleveraging of (core) European banks seeking to restore their capital positions. The GFC triggered regulatory reforms that were remarkable, especially with regard to the banking system. Nevertheless, the opportunity to fundamentally overhaul the regulatory regime in general and the global monetary order in particular was not seized. While regulatory reform has progressed incrementally during the last decade, the partial retreat of the USA from multilateralism has brought this issue back onto the table.